Common PHP Errors You Will Encounter - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"Do you want to be a web developer? Do you need to brush up on your PHP skills? Then you're in the right place! Perfect for beginners and experienced PHP developers alike, the PHP Programming for Absolute Beginners course takes you from absolute beginner to understanding the basics of PHP in just a few hours. You will learn everything about the basics of PHP programming using real world examples."--Resource description page.
Title from resource description page (viewed December 9, 2014)
Presenter, Stone River eLearning.
Keywords: PHP (Computer program language); Electronic books